New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Beyond pyrolysis optimization: a systematic review revealing feedstock acquisition and methodological standardization as critical barriers to biochar commercialization - R. B. Sherly Priyanka; Uday Shashikumar; Pei-Chien Tsai; Swapnil Gurrani; Gangadhar Andaluri; Cheng-Di Dong; Chyi-How Lay; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Clean Technologies and Environmental Policy, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

A temperate group living in the subtropics: evolutionary history and integrative taxonomy of the pseudoscorpion genus Allochthonius Chamberlin, 1929 (Pseudoscorpiones: Pseudotyrannochthoniidae) in Taiwan - Hsiang-Yun Lin; Danilo Harms; Ren-Chung Cheng; Chih-Han Chang (Organisms Diversity & Evolution, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Stable network complexity between bacterial community and dissolved organic matter remains under three-year consecutive nitrogen addition - Xiaochun Yuan; Quanxin Zeng; Qiufang Zhang; Cheng-Chung Liu; Junjian Wang; Liang Zeng; Kaimiao Lin; Chaoliang Chen; Weifeng Guo; Jiacong Zhou; Juyan Cui; Xiaoli Gao; et al. (Applied Soil Ecology, 2026)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Physicochemical properties on the bone of hairtail (Trichiurus lepturus) under various treatments of cooking pressure and vinegar - Huey-Jine Chai; Shang-Ta Wang; Yun-En Chung; Yi-Ting Pan; Yu-Cheng Lin; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2025)

Integrated assessment of wind energy's emission and meteorological effects on PM2.5 in Taiwan - I-Chun Tsai; Pei-Rong Hsieh; Cheng-Wei Lin; Chung-Cheh Chou; Chia-Ying Tu; Chao-Tzuen Cheng; Huang-Hsiung Hsu (Journal of Environmental Management, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Sediment characteristics affecting natural radionuclide distribution and radiological assessment in a tropical wetland near Maanshan Nuclear Power Plant, Southern Taiwan - Ting-Chien Chen; Yi-Lung Yeh; Fan-Cheng Zeng; Chih-Chung Lin; Zhi-Mou Chen; Wei-Hsiang Huang (Environmental Monitoring and Assessment, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Adaptation and carbon reduction for petroleum contaminated soil remediation in response to climate change-a case study of phytoremediation combined with biochar - Pei-Cheng Cheng; Min-Siou Lin; Chin-Yuan Huang; Shu-Fen Cheng; Yuan-Chung Lin (Journal of Environmental Management, 2025)

Carbon nanotube/two-dimensional metal–organic framework composites with enhanced thermoelectric performances for thermoelectric generators - Cheng-Yuan Lin; Jhe-Wei Chang; Meng-Hao Lin; Kuan-Chu Wu; Shao-Huan Hong; Jhih-Min Lin; Chung-Wei Kung; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Impact of ethanol-gasoline implementation on regulated and unregulated emissions from Euro 3–5 standard vehicles over the WLTP driving cycle - Syu-Ruei Jhang; Guor-Cheng Fang; Way Lee Cheng; Kun-Yeh Lee; Yuan-Chung Lin (Environmental Monitoring and Assessment, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Comprehensive evaluation of air quality: incense burning and night market emissions in Kaohsiung, Taiwan, using the ISCST3 air quality model - Pei-Cheng Cheng; Kassian T. T. Amesho; Yin-Cheng Huang; Yuan-Chung Lin; Feng-Chih Chou; Tsu-Nai Wang; Pei-Shih Chen; Kang-Shin Chen; Ken-Lin Chang; Chien-Hung Lee (Air Quality, Atmosphere & Health, 2025)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Investigation of the abasic sites induced by hydrogen peroxide and methyl methanesulfonate in calf thymus DNA and BEAS-2B cells - Dat Thanh Dinh; Gilang Putra Bahari; Qi Xu; Cheng-Hao Wei; Dar-Ren Chen; Wei-Chung Hsieh; Po-Hsiung Lin (Toxicology Letters, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Seismic rehabilitation of RC frames with innovative precast U-shaped UHPC jackets: Experimental evaluation and computational simulation - Chung-Chan Hung; Chin-Cheng Lin; Tuong Dat Dinh Do (Engineering Structures, 2024)

Advances in perfluoro-alkylated compounds (PFAS) detection in seafood and marine environments: A comprehensive review on analytical techniques and global regulations - Prasath Ramasamy Chandrasekaran; Jeganathan Chinnadurai; Yee Cheng Lim; Chiu-Wen Chen; Pei-Chien Tsai; Po-Chin Huang; Mohsen Gavahian; Gangadhar Andaluri; Cheng-Di Dong; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Cellulose acetate-coated capacitive sensor for determining carbon-cycle enzymes activity and as a microbial Indicator for soil health - Chung-Ting Cheng; Yu-Lin Wu; Yung-Te Hou; Tzong-Jih Cheng (Science of The Total Environment, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Mild chemical recycling of carbon fiber-reinforced epoxy composites in aqueous buffers and development of hydrothermally recyclable vitrimer composites from recyclates - Cheng Hao; Baoming Zhao; Lin Shao; Yiding Cao; Mingen Fei; Wangcheng Liu; Tuan Liu; Yu-Chung Chang; Kevin L. Simmons; Jinwen Zhang (Resources, Conservation and Recycling, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Mineralization of SF6 and NF3 fluorinated compounds for greenhouse gas abatement by oxalates - Ndumiso Vukile Mdlovu; Kuen-Song Lin; Cheng-Yang Tang; Wei-Chung Chen; Jamshid Hussain (Chemosphere, 2024)

Enhanced photodegradation of pentafluoropropionic acid (PFPA) via TiO2-synthetic zeolite composites: A sustainable approach for effective defluorination - Subham Halder; Feng-Chih Chou; Tsz-Kin Wan; Yi-Tien Tsai; Pei-Cheng Cheng; Yuan-Chung Lin (Journal of Water Process Engineering, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

Potential beneficial effects of long-term aspirin use on the prevalence of colorectal cancer: a population-based study of the US Nationwide Inpatient Sample - Ko-Chao Lee; Kuan-Chih Chung; Hong-Hwa Chen; Kung-Chuan Cheng; Kuen-Lin Wu; Ling-Chiao Song (Cancer Causes & Control, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Highly effective synthesis of 5-hydroxymethylfurfural from lignocellulosic biomass over a green and one-pot reaction in biphasic system - Quang Tam Huynh; Chong-Ting Zhong; Qing Huang; Yuan-Chung Lin; Ku-Fan Chen; Chien-Sen Liao; Cheng-Di Dong; Ken-Lin Chang (Bioresource Technology, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

First successful production of adult corals derived from cryopreserved larvae - Arah Narida; Sujune Tsai; Wen-Chung Hsieh; Zhi-Hong Wen; Li-Hsueh Wang; Cheng-Liang Huang; Chiahsin Lin (Frontiers in Marine Science, 2023)
Coral reefs worldwide are declining due to increasing concentrations of greenhouse gases, which, combined with local anthropogenic pressure, are exacerbating unprecedented mass coral bleaching. For corals to survive, restoring coral reefs through cryopreservation is crucial. The aim of this study was to vitrify and laser-warm Stylophora pistillata planulae to allow for feasible settlement, post-settlement survival, and the production of adult corals. The no-observed-effect concentrations were used to determine the best cryoprotective agents for S. pistillata . The larvae were then subjected to cooling and nanolaser warming (300 V, 10 ms pulse width, 2 mm beam diameter) by using two vitrification solutions (VSs; VS1: 2 M dimethyl sulfoxide and 1 M ethylene glycol and VS2: 2M EG and 1M DMSO and gold nanoparticles. The results revealed that VS1-treated larvae had a higher vitrification rate (65%), swimming rate (23.1%), settlement rate (11.54%), and post settlement survival rate (11.54%) than those treated with VS2. Seasonal variations also affected the cryopreservation of the planulae; VS1 was more favorable for the planulae in spring than in fall. Although laser-warmed larvae developed slower morphologically than their controlled counterparts, the production of adult S. pistillata corals from cryopreserved larvae was achieved. The proposed technique can improve the cryopreservation of corals and advance efforts to protect endangered coral species.

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Microbiome reengineering by four environmental factors for the rapid biodegradation of trichloroethylene - Yu-Hsuan Cheng; Shu-Chi Chang; Yan-Lin Lai; Chung-Chi Hu (Journal of Environmental Management, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Gas-phase and PM2.5-bound phthalates in nail salons: characteristics, exposure via inhalation, and influencing factors - Chia-Ling Chang; Hui-Tzu Chen; Chung-Yu Chen; En-Yu Chen; Kuan-Ting Lin; Chien-Cheng Jung (Environmental Science and Pollution Research, 2023)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Predicting Lumbar Vertebral Osteopenia Using LvOPI Scores and Logistic Regression Models in an Exploratory Study of Premenopausal Taiwanese Women - Chun-Wen Chen; Yi-Jui Liu; Shao-Chieh Lin; Chien-Yuan Wang; Wu-Chung Shen; Der-Yang Cho; Tung-Yang Lee; Cheng-Hsuan Juan; Cheng-En Juan; Kai-Yuan Cheng; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2022)
Purpose To propose hybrid predicting models integrating clinical and magnetic resonance imaging (MRI) features to diagnose lumbar vertebral osteopenia (LvOPI) in premenopausal women. Methods This prospective study enrolled 101 Taiwanese women, including 53 before and 48 women after menopause. Clinical information, including age, body height, body weight and body mass index (BMI), were recorded. Bone mineral density (BMD) was measured by the dual-energy X-ray absorptiometry. Lumbar vertebral fat fraction (LvFF) was measured by MRI. LvOPI scores (LvOPISs) comprising different clinical features and LvFF were constructed to diagnose LvOPI. Statistical analyses included normality tests, linear regression analyses, logistic regression analyses, group comparisons, and diagnostic performance. A P value less than 0.05 was considered as statistically significant. Results The post-menopausal women had higher age, body weight, BMI, LvFF and lower BMD than the pre-menopausal women (all P < 0.05). The lumbar vertebral osteoporosis group had significantly higher age, longer MMI, and higher LvFF than the LvOPI group (all P < 0.05) and normal group (all P < 0.005). LvOPISs (AUC, 0.843 to 0.864) outperformed body weight (0.747; P = 0.0566), BMI (0.737; P < 0.05), age (0.649; P < 0.05), and body height (0.5; P < 0.05) in diagnosing LvOPI in the premenopausal women. Hybrid predicting models using logistic regression analysis (0.894 to 0.9) further outperformed all single predictors in diagnosing LvOPI in the premenopausal women ( P < 0.05). Conclusion The diagnostic accuracy of the LvOPI can be improved by using our proposed hybrid predicting models in Taiwanese premenopausal women.

Correction to: Effects of cryopreservation on the ultrastructure of coral larvae - Luca Cirino; Sujune Tsai; Li-Hsueh Wang; Wen-Chung Hsieh; Cheng-Liang Huang; Zhi-Hong Wen; Chiahsin Lin (Coral Reefs, 2022)

Effects of nitrogen addition on the concentration and composition of soil-based dissolved organic matter in subtropical Pinus taiwanensis forests - Xiaochun Yuan; Juyan Cui; Kaimiao Lin; Cheng-Chung Liu; Jiacong Zhou; Qiufang Zhang; Quanxin Zeng; Lianzuan Wu; Yue Wu; Kongcan Mei; Huiying Lin; Huan Xie; et al. (Journal of Soils and Sediments, 2022)

Assessment of potential sediment disasters and resilience management of mountain roads using environmental indicators - Chao-Yuan Lin; Yuan-Chung Lai; Shao-Wei Wu; Fan-Chung Mo; Cheng-Yu Lin (Natural Hazards, 2022)
In recent years, extreme rainfall events occur frequently, causing serious watershed sediment disasters, destroying mountain roads, and endangering the safety of residents' lives and property. This study aims to deal with the spatial change of potential sediment movement on the road slope pre-disaster and to screen disaster hot spots for early warning and control system. The conceptual model is used to simulate the distribution of primary and/or derived disasters on a watershed scale to assess the impact of sediment disasters caused by heavy rain event. Correlation analysis shows that the models in assessment of primary disaster and derived disaster are significantly correlated with the collapse ratio and disaster ratio, respectively. Since the primary disaster has been considered when calculating the derived disaster risk, the terrain subdivision along Provincial Highway 21 (Tai-21) is extracted to understand the derived sediment disaster on the road slope. The model can effectively evaluate the road sections prone to disasters. According to the risk level, the hot spot of road slope disasters and the management of disaster resilience are determined and can be the reference for disaster prevention and control.

Effects of cryopreservation on the ultrastructure of coral larvae - Luca Cirino; Sujune Tsai; Li-Hsueh Wang; Wen-Chung Hsieh; Cheng-Liang Huang; Zhi-Hong Wen; Chiahsin Lin (Coral Reefs, 2022)

The effects of immersive garden experience on the health care to elderly residents with mild-to-moderate cognitive impairment living in nursing homes after the COVID-19 pandemic - Chung-Heng Hsieh; Cheng-Min Chen; Ju-Yuan Yang; Yen-Ju Lin; Man-Li Liao; Ke-Hsin Chueh (Landscape and Ecological Engineering, 2022)

Investigating the Transcriptomic and Expression Presence-Absence Variation Exist in Japanese Eel (Anguilla japonica), a Primitive Teleost - Yung-Sen Huang; Chung-Yen Lin; Wen-Chih Cheng (Marine Biotechnology, 2021)

Rac1 and Akt Exhibit Distinct Roles in Mediating Aβ-Induced Memory Damage and Learning Impairment - Kuan-Chung Cheng; Ying-Hao Chen; Chia-Lin Wu; Wang-Pao Lee; Chun Hei Antonio Cheung; Hsueh-Cheng Chiang (Molecular Neurobiology, 2021)

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Androgenic Sensitivities and Ovarian Gene Expression Profiles Prior to Treatment in Japanese Eel (Anguilla japonica) - Yung-Sen Huang; Wen-Chih Cheng; Chung-Yen Lin (Marine Biotechnology, 2021)

First report of cucurbit chlorotic yellows virus infecting melon, watermelon and wild melon in the Philippines - Hsin-Yi Chang; Li-Cheng Chen; Chung-Cheng Lin; Wen-Shi Tsai (Journal of Plant Pathology, 2021)

Phylogeny, recombination, and invasiveness of group B Streptococcus revealed by genomic comparisons of its global strains - Enze Lin; Shengmei Zou; Yue Wang; Chien-Chung Lee; Cheng-Hsun Chiu; Ye Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Advanced psychometric testing on a clinical screening tool to evaluate insomnia: sleep condition indicator in patients with advanced cancer - Chung-Ying Lin; Andy S. K. Cheng; Vida Imani; Mohsen Saffari; Maurice M. Ohayon; Amir H. Pakpour (Sleep and Biological Rhythms, 2020)
Purpose To examine the psychometric properties of the Sleep Condition Indicator (SCI) using different psychometric approaches [including classical test theory, Rasch models, and receiver operating characteristics (ROC) curve] among patients with advanced cancer. Methods Through convenience sampling, patients with cancer at stage III or IV ( n = 859; 511 males; mean ± SD age = 67.4 ± 7.5 years) were recruited from several oncology units of university hospitals in Iran. All the participants completed the SCI, Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), and Edmonton Symptom Assessment Scale (ESAS). In addition, 491 participants wore an actigraph device to capture objective sleep. Results Classical test theory [factor loadings from confirmatory factor analysis = 0.76–0.89; test–retest reliability = 0.80–0.93] and Rasch analysis [infit mean square (MnSq) = 0.63–1.31; outfit MnSq = 0.61–1.23] both support the construct validity of the SCI. The SCI had significant associations with ISI, PSQI, ESS, HADS, GHQ, and ESAS. In addition, the SCI has satisfactory area under ROC curve (0.92) when comparing a gold standard of insomnia diagnosis. Significant differences in the actigraphy measure were found between insomniacs and non-insomniacs based on the SCI score defined by ROC. Conclusion With the promising psychometric properties shown in the SCI, healthcare providers can use this simple assessment tool to target the patients with advanced cancer who are at risk of insomnia and subsequently provide personalized care efficiently.

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

Development of a Direction-Oriented Motion and Short-Sitting and Lying Tai Chi (DOM-SSLTC) Model for Function Recovery in Stroke Patients - Lian-Hui Lee; Hwai-Ting Lin; Nai-Wen Tsai; Yung-Chieh Yen; Cheng-Hsien Lu; Chun-Chung Lui; Hsien-Ming Chung; Kun-Chang Tsai; Shih-Pin Hsu; Huan-Wen Tsui (Journal of Medical and Biological Engineering, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Yi-Wen Li; Chung-Hsing Wang; Chao-Jung Chen; Charles C. N. Wang; Cheng-Li Lin; Wai-Kok Cheng; Hsin-Yi Shen; Yun-Ping Lim (Archives of Toxicology, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Assessment of Land Subsidence and Climate Change Impacts on Inundation Hazard in Southwestern Taiwan - Hsiao‐Wen Wang; Cheng‐Wei Lin; Chun‐Yao Yang; Chung‐Feng Ding; Hwung‐Hweng Hwung; Shih‐Chun Hsiao (Irrigation and Drainage, 2018)
Excessive extraction of groundwater resulting in serious land subsidence as well as intensified rainfall and storm surges due to climate change complicate the flooding problems in southwest Taiwan. A coupled set of different models was proposed to analyze the effect of inundation risk considering land subsidence and climate change. Three models, including the groundwater flow model, land subsidence model, and the physiographic drainage–inundation model, were used in this study, enabling simulations of different considerations. The results revealed that more severe flooding would result from land subsidence and climate change. The findings of a 21% increase in flood area with an inundation depth greater than 1.5 m for 200‐yr return period events clearly showed more severe flooding would result from land subsidence. The flooding in those severely subsiding areas would increase in a range from 3.4 to 21.5% when further considering climate change. While the simulation results revealed that the flood area could be decreased by as much as 50% taking into account the implemented policies, the coastal region would still be exposed to a high risk of being flooded. It thus suggests that policies focusing on infrastructure would be insufficient, and river basin management as well as spatial planning should be investigated further. Copyright © 2018 John Wiley & Sons, Ltd.

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

miRNA Expression Change in Dorsal Root Ganglia After Peripheral Nerve Injury - Hsueh-Ling Chang; Hung-Chen Wang; Yi-Ta Chunag; Chao-Wen Chou; I-Ling Lin; Chung-Sheng Lai; Lin-Li Chang; Kuang-I Cheng (Journal of Molecular Neuroscience, 2017)

Novel interaction between CCR4 and CAF1 in rice CCR4–NOT deadenylase complex - Wei-Lun Chou; Yue-Lin Chung; Jhen-Cheng Fang; Chung-An Lu (Plant Molecular Biology, 2017)

Identification of Vibrio parahaemolyticus in Seafood by Multiplex PCR - Chung-Saint Lin; Tser-Sheng Lin; Din-Yuan Yu; Yi-Cheng Su; Yung-Hsiang Tsai (Journal of Aquatic Food Product Technology, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease - Chung-Min Liao; Bo-Chun Wu; Yi-Hsien Cheng; Shu-Han You; Yi-Jun Lin; Nan-Hung Hsieh (Environmental Science and Pollution Research, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Experiments on channel evolution due to dam removal in Taiwan - Hsiao-Wen Wang; Ying-Che Cheng; Chung-Yi Lin (Journal of Mountain Science, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Trace Element, Antioxidant Activity, and Lipid Peroxidation Levels in Brain Cortex of Gerbils After Cerebral Ischemic Injury - Kwang-Ming Fang; Fu-Chou Cheng; Yeou-Lih Huang; Shu-Ying Chung; Zhong-Yang Jian; Ming-Cheng Lin (Biological Trace Element Research, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Modeling and assessment of bridge structure for seismic hazard prevention - Jeng-Wen Lin; Cheng-Wu Chen; Shang-Heng Chung (Natural Hazards, 2012)

Evaluation of the optimal strategy for ex situ bioremediation of diesel oil-contaminated soil - Ta-Chen Lin; Po-Tsen Pan; Chiu-Chung Young; Jo-Shu Chang; Tsung-Chung Chang; Sheng-Shung Cheng (Environmental Science and Pollution Research, 2011)

Traceless synthesis of diketopiperazine fused tetrahydro-β-carbolines on soluble polymer support - Kaushik Chanda; Cheng-Ting Chou; Jin-Ji Lai; Shu-Fen Lin; Gorakh S. Yellol; Chung-Ming Sun (Molecular Diversity, 2011)

Erratum to: Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tzeng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tseng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Isolation and characterization of 15 microsatellite loci from Caridina gracilipes (Atyidae, Decapoda) - Chiao-Chuan Han; Cheng-Sheng Chang; Tzen-Yuh Chiang; Ping-Han Chung; Hung-Du Lin (Conservation Genetics, 2009)

A chaos-based visual encryption mechanism for clinical EEG signals - Chin-Feng Lin; Cheng-Hsing Chung; Jia-Hui Lin (Medical & Biological Engineering & Computing, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Shrimp shell as a potential sorbent for removal of arsenic from aqueous solution - Ming-Chao Lin; Chung-Min Liao; Ying-Cheng Chen (Fisheries Science, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Expression of a Bacillus thuringiensis toxin (cry1Ab) gene in cabbage (Brassica oleracea L. var. capitata L.) chloroplasts confers high insecticidal efficacy against Plutella xylostella - Cheng-Wei Liu; Chin-Chung Lin; Jinn-Chin Yiu; Jeremy J. W. Chen; Menq-Jiau Tseng (Theoretical and Applied Genetics, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Expression of a Bacillus thuringiensis toxin (cry1Ab) gene in cabbage (Brassica oleracea L. var. capitata L.) chloroplasts confers high insecticidal efficacy against Plutella xylostella - Cheng-Wei Liu; Chin-Chung Lin; Jinn-Chin Yiu; Jeremy J. W. Chen; Menq-Jiau Tseng (Theoretical and Applied Genetics, 2008)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Stable chloroplast transformation in cabbage (Brassica oleracea L. var. capitata L.) by particle bombardment - Cheng-Wei Liu; Chin-Chung Lin; Jeremy J. W. Chen; Menq-Jiau Tseng (Plant Cell Reports, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Atmosphic pollutants study of particles ionic species during high wind speed (>7 m s-1) near Taiwan strait in central Taiwan from 2004 to 2005 - Guor-Cheng Fang; Yuh-Shen Wu; Wen-Jhy Lee; Chi-Kwong Lin; Chung-Po Lin (Environmental Monitoring and Assessment, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Tamoxifen-induced Ca 2+ mobilization in bladder female transitional carcinoma cells - Hong-Tai Chang; Jong-Khing Huang; Jue-Long Wang; Jin-Shiung Cheng; Kam-Chung Lee; Yuk-Keung Lo; Muh-Chiou Lin; Kwong-Yui Tang; Chung-Ren Jan (Archives of Toxicology, 2001)